2013
DOI: 10.1371/journal.pone.0073665
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Room Temperature Plasma Jets Facilitate Oxidative and Nitrative Stress and Lead to Endoplasmic Reticulum Stress Dependent Apoptosis in HepG2 Cells

Abstract: Atmospheric pressure room temperature plasma jets (APRTP-Js) that can emit a mixture of different active species have recently found entry in various medical applications. Apoptosis is a key event in APRTP-Js-induced cellular toxicity, but the exact biological mechanisms underlying remain elusive. Here, we explored the role of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in APRTP-Js-induced apoptosis using in vitro model of HepG2 cells. We found that APRTP-Js facilitated the accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 59 publications
(55 reference statements)
5
81
0
Order By: Relevance
“…To address the enhanced synthesis of secretory proteins when the ER is overloaded, molecular compensatory mechanisms 1) upregulate ER chaperones; 2) reduce translation, decreasing the load of new protein synthesis, and 3) degrade misfolded proteins within the ER [10]. When ER stress conditions persist, the initiation of apoptotic processes is promoted by the transcriptional induction of C/EBP homologous protein (CHOP/GADD153) [11], the caspase-12-dependent pathway [12], and activation of the c-Jun NH2-terminal kinase (JNK)-dependent pathway [13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the enhanced synthesis of secretory proteins when the ER is overloaded, molecular compensatory mechanisms 1) upregulate ER chaperones; 2) reduce translation, decreasing the load of new protein synthesis, and 3) degrade misfolded proteins within the ER [10]. When ER stress conditions persist, the initiation of apoptotic processes is promoted by the transcriptional induction of C/EBP homologous protein (CHOP/GADD153) [11], the caspase-12-dependent pathway [12], and activation of the c-Jun NH2-terminal kinase (JNK)-dependent pathway [13]. …”
Section: Discussionmentioning
confidence: 99%
“…One major pathway of the UPR increases the expression of ER-localised molecular chaperones, such as GRP78, which can contribute to repairing unfolded proteins. The induction of GRP78 has been widely used as a marker for ER stress and initiation of the UPR [12]. Furthermore, GRP78 serves as a master modulator for the UPR network by binding to the ER stress sensors, including PKR-like ER kinase (PERK), inositol requiring 1 (IRE1), and transcription factor 6 (ATF6), inhibiting their activation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators reported that the effects of LTP on biological cells (prokaryotes and eukaryotes) are mediated by reactive oxygen and nitrogen species (RONS) [11,12,[59][60][61][62][63][64][65][66]. These species include hydroxyl, OH, atomic oxygen, O, singlet delta oxygen, O 2 ( 1 ∆), superoxide, O 2 − , hydrogen peroxide, H 2 O 2 , and nitric oxide, NO.…”
Section: Mechanisms Of Biological Action Of Ltp: Brief Summarymentioning
confidence: 99%
“…In particular, the research of CAP as a potential oncotherapeutic approach has thrived over the past decade and the mechanism is been increasingly understood [12][13][14][15][16]. It is widely reported that CAP deactivated more than 20 types of cancer in vitro by inducing apoptosis [17][18][19], cell cycle arrest [20][21][22], endoplasmic reticulum stress [23,24] and DNA damage [25][26][27]. CAP has also been shown to significantly reduce tumor volume in an in vivo murine model following s phase cell cycle arrest and apoptosis [28].…”
Section: Introductionmentioning
confidence: 99%